Politeness in ancient Greek and Latin - Unceta Gómez, Luis ca. 20./21. Jh; Berger, Łukasz 1987- (Cambridge University Press, 2023)
"Politeness serves to manage social relations or is wielded as an instrument of power. Through good manners, people demonstrate their educational background and social rank. This is the first book to bring together the most recent scholarship on politeness and impoliteness in Ancient Greek and Latin, signalling both its universal and its culture-specific traits. Leading scholars analyse texts by canonical classical authors (including Plato, Cicero, Euripides, and Plautus), as well as non-literary sources, to provide glimpses into the courtesy and rudeness of Greek and Latin speakers. A wide range of interdisciplinary approaches is adopted, namely pragmatics, conversation analysis, and computational linguistics. With its extensive introduction, the volume introduces readers to one of the most dynamic fields of Linguistics, while demonstrating that it can serve as an innovative tool in philological readings of classical texts"--
Contributions based on papers presented at the conference Approaches to Greek and Latin im/politeness held at the Universidad Autónoma de Madrid in June 2017
Keywords: Griechisch; Honorativ; Latein; Politeness (Linguistics) / Congresses; Classical languages / Honorific / Congresses; Greek language / Honorific / Congresses; Latin language / Honorific / Congresses; Classical literature / History and criticism / Congresses; Etiquette in literature / Congresses; FOREIGN LANGUAGE STUDY / Ancient Languages (see also Latin); Aufsatzsammlung; Konferenzschrift -- Universidad Autónoma de Madrid -- 2017 -- Madrid